ChemInform Abstract: A Review of Enzymes and Microbes for Lignocellulosic Biorefinery and the Possibility of Their Application to Consolidated Bioprocessing Technology. Issue 39 (5th September 2013) - Hasunuma, Tomohisa; Okazaki, Fumiyoshi; Okai, Naoko; Hara, Kiyotaka Y.; Ishii, Jun; Kondo, Akihiko
Abstract Review: 74 refs.